2019
DOI: 10.1177/0829573519880063
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Relationship Between ADHD Symptomatology and Amotivation in the Undergraduate Population: The Role of Basic Psychological Need Frustration

Abstract: Recent research has shown that undergraduate students who experience both clinical and subclinical attention-deficit/hyperactivity disorder (ADHD) struggle academically. Furthermore, these students have cited academic amotivation as a factor in their academic difficulties. Self-determination theory (SDT) posits that a lack of motivation—known as amotivation—may be the result of the frustration of the basic psychological needs—autonomy, competence, and relatedness. For this reason, the current study examined wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
1
11
1
Order By: Relevance
“…For example, in several instances, the positive effect of need satisfaction was undone by the negative effects of need frustration. Insomuch as frustration has been understudied relative to need satisfaction (Oram et al, 2020), previous results may be misspecified and overrepresenting the benefits of need satisfaction. We encourage future research to consider both satisfaction and frustration when examining BPNs.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in several instances, the positive effect of need satisfaction was undone by the negative effects of need frustration. Insomuch as frustration has been understudied relative to need satisfaction (Oram et al, 2020), previous results may be misspecified and overrepresenting the benefits of need satisfaction. We encourage future research to consider both satisfaction and frustration when examining BPNs.…”
Section: Discussionmentioning
confidence: 98%
“…In one of these studies ( Rogers & Tannock, 2018 ), students in grades 1 to 4 that have high levels of ADHD symptoms reported lower perceptions of autonomy support, competence, and relatedness to their teacher, compared to their asymptomatic peers. In the second study ( Oram et al, 2020 ), self-reported ADHD symptomatology in a sample of undergraduate students was positively and moderately associated with autonomy, competence, and relatedness need frustration.…”
Section: Inattention Symptoms and Pns At Schoolmentioning
confidence: 94%
“…From the participant sample, 73.3% identified as female ( n = 452), 74.7% reported being between the ages of 18–20 years old ( n = 461), 59.5% and 24.8% reported being in their first and second year of undergraduate studies respectively ( n = 520). As per threshold criteria on the short‐form screener of the Adult ADHD Self‐Report Scale version 1.1 (ASRS‐v1.1; World Mental Health Composite International Diagnostic Interview Organization, 2003), 18.5% of participants scored 15.0 or above ( n = 114), thus they were considered to be at risk for ADHD (Oram et al, 2019; Salla et al, 2019). Only 3.1% of the participants reported they were currently taking prescribed medication for attention difficulties ( n = 19).…”
Section: Methodsmentioning
confidence: 99%
“…Mental Health Composite International Diagnostic Interview Organization, 2003), 18.5% of participants scored 15.0 or above (n = 114), thus they were considered to be at risk for ADHD (Oram et al, 2019;Salla et al, 2019). Only 3.1% of the participants reported they were currently taking prescribed medication for attention difficulties (n = 19).…”
Section: Participantsmentioning
confidence: 99%